The effects of after-school programs on maternal employment - Fabian Dehos; Marie Paul (Deutsches Institut für Wirtschaftsforschung (DIW), 2017)
This paper evaluates the impact of a massive expansion of after-school programs (ASPs) on the labor market participation of mothers with primary school children in the West German context of relatively low full-time employment rates. Using an instrumental variables approach we exploit regional and temporal variation in the provision of federal ASP starting grants by a nationwide investment program. Results suggest that additional ASP places had no effect on working hours or the employment probability of mothers with primary school children.
Keywords: J13; J21; J22; 330; maternal employment; after-school programs; instrumental variables